2014
DOI: 10.1159/000356521
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Infection Alters Mood and Short-Term Memory as well as Levels of Neurotransmitters and Cytokines in the Mouse Hippocampus

Abstract: Helminthic infections are important causes of morbidity and mortality in many developing countries, where children bear the greatest health burden. The ability of parasites to cause behavioral changes in the host has been observed in a variety of host-parasite systems, including the Taenia crassiceps-mouse model. In murine cysticercosis, mice exhibit a disruption in the sexual, aggressive and avoidance predator behaviors. Objective: The present study was conducted to characterize short-term memory and depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 58 publications
4
19
0
Order By: Relevance
“…Strikingly, CD4 + CD25 + FoxP3 + cells were not found to be elevated on either strain, suggesting that this CD4 + cell population does not play a major role in parasite permissiveness in experimental cysticercosis, thus indicating the importance of AAMs in tolerance induction to this parasite. Moreover, the presence of increased numbers of Tregs was addressed using Treg reporter mice, C.Cg‐Foxp3tm1Tch/J, and again increased numbers of Tregs were not detected even in chronic infections . However, studies with T. solium were reported by finding higher numbers of Tregs , indicating subtle divergences between the immunoregulation of T. solium and T. crassiceps cysticercosis.…”
Section: Convergence and Divergence In Immunoregulatory Mechanisms Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, CD4 + CD25 + FoxP3 + cells were not found to be elevated on either strain, suggesting that this CD4 + cell population does not play a major role in parasite permissiveness in experimental cysticercosis, thus indicating the importance of AAMs in tolerance induction to this parasite. Moreover, the presence of increased numbers of Tregs was addressed using Treg reporter mice, C.Cg‐Foxp3tm1Tch/J, and again increased numbers of Tregs were not detected even in chronic infections . However, studies with T. solium were reported by finding higher numbers of Tregs , indicating subtle divergences between the immunoregulation of T. solium and T. crassiceps cysticercosis.…”
Section: Convergence and Divergence In Immunoregulatory Mechanisms Inmentioning
confidence: 99%
“…Also neuropeptides are able to affect the host–parasite interaction in taeniids. It has been reported that Taenia infections can alter neurotransmission function in the hippocampus and some neuropeptides can modulate local responses, specifically in granulomas encapsulating metacestodes of T. crassiceps . A series of studies have shown that substance P, a neuropeptide that can be released by nerves and inflammatory cells, participates in inflammatory processes .…”
Section: Convergence and Divergence In Immunoregulatory Mechanisms Inmentioning
confidence: 99%
“…The authors suggested that the absence of a gut microbiota in these animals prevented the induction of the specific subset of pathogenic T helper type 17 cells and memory T helper type 1 cells that would target the tumour in normal mice . An interesting follow‐up study might investigate if the microbiota uses the immune system to influence mood and emotions, such as the way parasitic helminths have been shown to decrease aggression and short‐term memory in infected mice . Finally, studies into the ‘hunger hormone’ ghrelin have revealed that this peptide not only plays a significant role in appetite regulation and energy homeostasis but also exerts a significant modulatory effect on both mood and the immune system.…”
Section: Gut Feelings: Immunity Emotion and The Digestive Systemmentioning
confidence: 99%
“…101 An interesting follow-up study might investigate if the microbiota uses the immune system to influence mood and emotions, such as the way parasitic helminths have been shown to decrease aggression and short-term memory in infected mice. 102 Finally, studies into the 'hunger hormone' ghrelin have revealed that this peptide not only plays a significant role in appetite regulation and energy homeostasis but also exerts a significant modulatory effect on both mood and the immune system. Ghrelin-treated mice exhibit reduced inflammation and enhanced lymphocyte development in response to immune stimuli, while ghrelin knockout animals presented heightened anxiety and depressive behaviour when subjected to a variety of emotional stressors.…”
Section: Gut Feelings: Immunity Emotion and The Digestive Systemmentioning
confidence: 99%
“…Our results provide insight into the mechanisms by which neuroimmune interactions alter the acquisition of immunity against the human nematode parasite T. spiralis [22]. A study of the effects of myelin deprivation not only gives us knowledge of the role that myelin may have on different systems in the organism, but it also gives us tools to understand the relationship between different systems, in particular the CNS and immune system, which maintains a balance between them [23]. Understanding the interaction of these systems requires that we include all members of the participating systems.…”
Section: Discussionmentioning
confidence: 99%